Comercio, manufactura y servicios en Arequipa a inicios de la República - Betalleluz Meneses, Betford (Universidad del Pacífico, 2004)
The article analyzes the impact produced by the changes in national trade policies in Arequipa’s manufacturing, commerce, and service sectors at the beginning of the Republic. After the Independence, the economic protectionism was installed during the first decades promoted by the farmers from the north and mining entrepreneurs who were jealous of the competition from English, French, and American products. They preferred to protect the internal market with high tariffs. In the opposite side, the traders and farmers from the south were in favor of the free trade policies to rebuild the old viceroyal market with Bolivia and in order to export wool to Great Britain. The market opening was only achieved from 1836 to 1839 while the Peruvian-Bolivian Confederation lasted. Finally, the Peruvian economy opening was gotten in the middle of 1840 in the great guano’s age.